Effects of non-genetic factors on milk yield and chemical composition of milk from Holstein-Friesian cows - Şahin, Onur (Revista Colombiana de Ciencias Pecuarias, 2023)
Background: It is necessary to determine the extent and direction of environmental factors to accurately assess cow performance in terms of milk yield and milk components. Although many studies have explored environmental factors affecting milk yield, there is not enough information about the effects and direction of environmental factors on milk composition. Objective: To determine the effects of non-genetic factors, such as calving season, lactation number, lactation stage, animal age, and herd size on milk yield, chemical composition of raw milk, and Somatic Cell Count (SCC) in Holstein-Friesian cows. Methods: Data were obtained from 15,354 raw milk samples of 5,118 Holstein-Friesian cows at 276 dairy farms in Türkiye. The data analysis was performed using the General Linear Model (GLM) feature of the SPSS statistics program. Results: Mean fat (F), protein (P), dry matter (DM), lactose (L), urea (U), and Log10SCC values of milk were 3.74 ± 0.01, 3.19 ± 0.01, 11.36 ± 0.03, 4.32 ± 0.01%, 21.57 ± 0.28 mg/dL, and 5.244 ± 0.01 cells/mL, respectively. Peak milk yield (PMY), lactation milk yield (LMY), 305-day milk yield (305-d MY), and SCC values were 33.7 ± 0.13, 8,538.33 ± 89.64 kg, 6,479.42 ± 168.96 kg, and 224,164.34 ± 4,402.79 cells/mL, respectively. Conclusion: Dairy farms in Türkiye should improve protein, dry matter, and urea contents in milk and investigate in detail the relationship between raw milk urea, subclinical mastitis, and reproductive features.